Myocardial bridging: non-invasive diagnostics and management - S. A. Chepurnenko; G. V. Shavkuta; A. D. Nasytko (Кардиоваскулярная терапия и профилактика)
The article discusses a case of episodes of asymptomatic ST-T depression during exercise in a 37-year-old patient with complaints of irregular heartbeat, tachycardia up to 100 bpm, not related to exercise. According to contrast-enhanced multislice computed tomography, in the middle third, a muscle bridge with stenosis of up to 30% was found. The diagnosis was made: Congenital coronary artery anomaly: transmyocardial muscular bridge of the middle third of left anterior descending artery with stenosis up to 30%. Class 1 silent myocardial ischemia. Stage 0, class 0 chronic heart failure. Using non-invasive coronary imaging, it was possible to identify the cause of transient ST-T depression and to choose the appropriate therapy.